Kemampuan Pemodelan Matematika Melalui Pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) di SMK Yayasan Bakti Prabumulih - Monica Apriliana; Lusiana Lusiana; Jumroh Jumroh (Institut Agama Islam Negeri Curup, 2021)
This study aims to determine and describe the ability of mathematical modeling through the Indonesian Realistic Mathematics Education approach. The Indonesian Realistic Mathematical Education approach is a learning approach that uses real problems as the beginning of learning mathematics so that it is skilled in solving problems, so as to obtain essential knowledge and concepts from the learning material. The research method used in this research is a one-shot case study experiment. This research was conducted in class XI.TKJ SMK Yayasan Bakti Prabumulih Foundation in the 2020/2021 academic year, totaling 30 students. This type of research is descriptive quantitative. Data collection in this study used a test instrument in the form of description questions based on indicators of mathematical modeling ability. Based on the results of the study, it was found that the mathematical modeling skills of students through the Indonesian Realistic Mathematics Education approach reached an average percentage of 75.96%.